Design of 3-Dimensional Simulation in Marching Drill Multimedia Based for Junior High School Students - Sipahutar, Lahmudin (Institut Teknologi Bisnis AAS Indonesia, 2023)
With multimedia-based technology, this is one area that is commonly used in learning methods. Computers also provide 3-dimensional (3D) technology which can become a new interest for students in the teaching and learning process. One of them is Marching Training (PBB). This application discusses marching, the benefits and objectives and regulations of marching. Therefore, a tool is needed to help learn commands and marching rules. So that a child can more quickly capture and understand what is conveyed through an interesting picture. In this way, students' interest in learning can be more motivated and can increase children's knowledge in using computers. Design is a creative activity towards something new and useful that did not exist before. According to Al-Bahra (2005: 51), design is the ability to create several alternative problem solutions. Meanwhile, according to Azhar Susanto (2004: 332), design is a general and detailed specification of computer-based problem solving that has been selected during the analysis stage.